Essence And Purpose of Educational Philosophy: The Foundation Of Student Character Development - Suharry; Risha Febriyanti; Nizwardi Jalinus (AKADEMI TEKNIK ADI KARYA, 2024)
This article discusses the importance of philosophical foundations in coaching students in schools. This research uses quantitative methods of literature research types with primary sources from books, journals, articles, and other scientific sources. The results showed that the teacher's philosophical foundation in coaching students is very important to achieve the expected educational goals. Ki Hadjar Dewantara revealed that education guides all the natural forces that exist in children so that they can achieve the highest safety and happiness. Therefore, as educators and parents, we must be able to provide teaching and guidance on the growth and development of a child with content that is in accordance with the nature of children, the development of the times, and their age. In this study, it was also explained one form of student coaching with the restitution triangle method and its steps.